Edukasi Publik dengan Komunikasi Massa tentang Protokol Kesehatan dan Vaksin COVID-19 di Kabupaten Malinau - Permana, Lies; Rolantika, Widiya (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
COVID-19 has been countered in the community by implementing health protocols and providing COVID-19 vaccines in order to prevent transmission, morbidity, and mortality. This program is one of the promotion activities of using print media and mobile broadcasts to educate the public about health protocols and COVID-19 vaccines in mass. The goal of this project is to improve public access to health-related information and COVID-19 vaccines. The PRECEDE-PROCEED method has been used to plan the program, and the fishbone method has been used to analyze the reasons of the problem, followed by the implementation stage and evaluation. The activities leads to the formation of a collaboration with the District Health Office to create a variety of printed health promotion media, as well as the implementation of mobile broadcasts using official operational automobiles that directly target community. Several communities and health promotion officers from the local health office participated in the evaluation, which received a positive response using a simple online questionnaire instrument. Suggestions for relevant health organizations to keep improving IEC media with current information and mobile broadcasting operations so that they might reach out to other people in areas that are crowded but also have limited access to health information on a regular basis.